Analisis Semiotika Makna Kerinduan pada Lirik Lagu “Gala Bunga Matahari” Karya Sal Priadi - Wanda Indah Agustina; Diryo Suparto; Ike Desy Florina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article examines the meaning of longing in the lyrics of the song “Gala Bunga Matahari” by Sal Priadi through Roland Barthes semiotic analysis. The purpose of this article is to find the meaning of longing in the song by using Roland Barthes' theory which explains denotation meaning, connotation meaning, and mythical meaning. The research method used is interpretive qualitative method or inductive way of thinking, which is a way of thinking from specific to general. The data collection technique used is a document study, namely by searching and obtaining from various sources that contain the necessary data. The results of the semiotic study of the lyrics of the song “Gala Bunga Matahari” by Sal Priadi are first, the denotation meaning, the songwriter wants to convey a great feeling of longing for someone who is gone and wants to meet even if only in a dream in the form of a sunflower. This is evidenced in every stanza of the song explaining hope and longing for someone who is gone. Second, the connotation meaning, the songwriter feels sadness and hope in himself because he cannot meet again and hopes that loved ones get a good life in the afterlife. This is evidenced in the first, second, fourth and seventh stanzas. Third, the mythical meaning, the author wants to convey the message that the intense longing for a person who has passed away by trying to believe in the prayers that are sent for the happiness of the deceased and believe that we can continue life well, this longing and sadness can be treated by letting go, accepting, and believing. This is evidenced in the third, fifth, and eighth stanzas.